2018
DOI: 10.35308/jpt.v5i1.1026
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Komposisi Sampah Laut Di Pesisir Aceh Barat

Abstract: Marine Debris or Marine Liiter is a solid material that inadvertently or unintentionally left in the sea that has the impact of threatening the continuity and sustainability of marine life. Research on marine debris was conducted in West Aceh regency covering four coastal districts namely: Meurebo, Johan Pahlawan, Samatiga, and Arongan Lambalek. The purpose of this research is to identify the composition of marine debris in West Aceh district. So it can be as basic information to know the number and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
3
0
10
Order By: Relevance
“…Garbage in coastal areas is one of the most complex problems found in an area close to the beach or coast [16], [17]. Based on the type of waste found during the study, it showed that the dominant type of waste was derived from anthropogenic activities on the mainland, with the types of waste found such as glass plastic, plastic snack wrap, other plastic wrap and glass bottles.…”
Section: Community Activities In the Keramat Village Mananggu Districtmentioning
confidence: 99%
“…Garbage in coastal areas is one of the most complex problems found in an area close to the beach or coast [16], [17]. Based on the type of waste found during the study, it showed that the dominant type of waste was derived from anthropogenic activities on the mainland, with the types of waste found such as glass plastic, plastic snack wrap, other plastic wrap and glass bottles.…”
Section: Community Activities In the Keramat Village Mananggu Districtmentioning
confidence: 99%
“…Sampah yang banyak ditemukan di pesisir Pantai Sebalang dan Pantai Tanjung Selaki sebagian besar diduga berasal dari kegiatan pariwisata. Menurut Kusumawati et al (2018); Ryan et al (2009) Hasil pengukuran arus laut didapat bahwa pergerakan arus laut saat ketinggian perairan berada pada titik tertinggi (Pukul 09:00 WIB) dan terendah (Pukul 14:30 WIB) dimana arus laut yang didapatkan justru lebih lambat dibandingkan saat ketinggian perairan sedang megalami peningkatan (Pukul 12:00 WIB) ataupun penurunan (Pukul 16:00 WIB). Hasil tersebut didukung oleh Poerbandono dalam Anisa et al (2017) yang menyatakan bahwa gerakan arus laut maksimum terjadi ketika pergerakan permukaan air mulai meninggi ataupun mulai menurun, sedangkan kecepatan air minimum terjadi ketika permukaan perairan mencapai titik paling rendah atau surut.…”
Section: Kepadatan Sampahunclassified
“…Fiber dan Styrofoam ditemukan dengan total presentase masing-masing berjumlah 13,33% dan 6,07% (Gambar 3). Menurut Kusumawati (2018), sampah plastik adalah jenis sampah yang mudah terapung dan terbawa arus, oleh karena itu hal ini juga disampaikan oleh NOAA (2015) bahwa penelitian mengenai sampah laut di seluruh perairan dunia, jenis sampah plastik adalah jenis yang paling banyak dijumpai dan paling berbahaya bagi organisme laut.…”
Section: Komposisi Mesoplastikunclassified